Financial inclusion, financial management, and micro business performance - Risal Rinofah; Hasti Nugrahaning Tyas; Ratih Kusumawardhani (Universitas Sebelas Maret, 2022)
This study aims to determine the effect of financial inclusion, quality of financial management, and financial management on the financial performance of MSMEs at Wonosari Culinary Park, Gunungkidul. The strategy in this study uses a quantitative approach. The sampling technique used a saturated sampling method with a sample of 69 respondents and then tested. Quantitative data in this study is data sourced directly from respondents presented in the form of a Likert scale-data collection technique used to distribute questionnaires or questionnaires. The data processing statistical method used is descriptive statistics and Partial Least Square (PLS) with the SmartPLS version 3.0 program. The results show a significant effect of financial inclusion on financial performance, a significant effect of the quality of financial management on financial performance, and a significant effect of financial management on financial performance.